Acoustical evaluation of the Teatro Colón of Buenos Aires - Basso, Gustavo Jorge (2017)
The acoustical quality of the Teatro Colón of Buenos Aires as a symphonic auditorium, considered among the best of the world, is evaluated from different perspectives. From the results of opinion polls about the perceived sound by the audience and from physical measurements, some of its acoustical characteristics were identified. However, some discrepancies have been found between the values suggested by the methods to predict the acoustical quality of halls for music, such as Beranek’s Acoustical Quality Index, and the data collected. A digital model of the hall was developed in order to identify the origin of that inconsistency. From the outcomes of this tool, the results of the measurements and the aural prospection in the real hall, some of the causes of its particular acoustical behaviour have been found out. A specific combination of architectural features like the shape of the horseshoe, the height and depth of the boxes at the upper levels and the design of the proscenium seems to play an important role in this sense. In this work, only the acoustical quality of the main floor of the Teatro Colón is analysed.